Characteristics of gut microbiota profiles in Asian elephants (Elephas maximus) with gastrointestinal disorders - Klinhom, Sarisa; Kunasol, Chanon; Sriwichaiin, Sirawit; Kerdphoo, Sasiwan; Chattipakorn, Nipon; Chattipakorn, Siriporn C.; Thitaram, Chatchote (Scientific reports, 2025)
Colic and diarrhea are common gastrointestinal (GI) disorders in captive Asian elephants, which can severely impact health and lead to mortality. Gut dysbiosis, indicated by alterations in gut microbiome composition, can be observed in individuals with GI disorders. However, changes in gut microbial profiles of elephants with GI disorders have never been investigated. Thus, this study aimed to elucidate the profiles of gut microbiota in captive elephants with different GI symptoms. Fecal samples were collected from eighteen elephants in Chiang Mai, Thailand, including seven healthy individuals, seven with impaction colic, and four with diarrhea. The samples were subjected to DNA extraction and amplification targeting the V3-V4 region of 16S rRNA gene for next-generation sequencing analysis. Elephants with GI symptoms exhibited a decreased microbial stability, as characterized by a significant reduction in microbiota diversity within individual guts and notable differences in microbial community composition when compared with healthy elephants. These changes included a decrease in the relative abundance of specific bacterial taxa, in elephants with GI symptoms such as a reduction in genera Rubrobacter , Rokubacteria, UBA1819, Nitrospira , and MND1. Conversely, an increase in genera Lysinibacillus , Bacteroidetes_ BD2-2, and the family Marinifilaceae was observed when, compared with the healthy group. Variations in taxa of gut microbiota among elephants with GI disorders indicated diverse microbial characteristics associated with different GI symptoms. This study suggests that exploring gut microbiota dynamics in elephant health and GI disorders can lead to a better understanding of food and water management for maintaining a healthy gut and ensuring the longevity of the elephants.